Implementation of Restorative Justice in the Resolution of Theft Crimes Committed by Minors at the Denpasar City Police Resort - Adi Putra, Salit Ngurah Bagus; Bagiastra, I Nyoman (West Science Interdisciplinary Studies, 2025)
This study aims to (1) identify and analyze the implementation of Restorative Justice in resolving theft crimes committed by children at the Denpasar City Resort Police, and (2) identify and analyze the obstacles and efforts made by investigators in applying Restorative Justice. This research uses an empirical legal method with a descriptive approach. The research was conducted at the Denpasar City Resort Police. Data collection techniques included document study, observation, and interviews. The sampling technique used was non- probability sampling with purposive sampling for subject selection. The data were analyzed using qualitative techniques. The results showed that (1) the implementation of Restorative Justice in resolving child theft crimes at the Denpasar City Resort Police was in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, but the process has not been fully effective due to communication barriers and lack of mutual understanding between the involved parties. (2) The obstacles encountered are classified into internal obstacles, such as legal limitations, lack of inter-agency coordination, and insufficient facilities and infrastructure; and external obstacles, including the child as perpetrator, the victim’s unwillingness to reconcile, difficulty in finding witnesses, and public perception. The efforts made by investigators include building intensive communication and mutual understanding with all involved parties to support the successful implementation of restorative approaches.